6x+5=9x-7

Simple and best practice solution for 6x+5=9x-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x+5=9x-7 equation:


Simplifying
6x + 5 = 9x + -7

Reorder the terms:
5 + 6x = 9x + -7

Reorder the terms:
5 + 6x = -7 + 9x

Solving
5 + 6x = -7 + 9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9x' to each side of the equation.
5 + 6x + -9x = -7 + 9x + -9x

Combine like terms: 6x + -9x = -3x
5 + -3x = -7 + 9x + -9x

Combine like terms: 9x + -9x = 0
5 + -3x = -7 + 0
5 + -3x = -7

Add '-5' to each side of the equation.
5 + -5 + -3x = -7 + -5

Combine like terms: 5 + -5 = 0
0 + -3x = -7 + -5
-3x = -7 + -5

Combine like terms: -7 + -5 = -12
-3x = -12

Divide each side by '-3'.
x = 4

Simplifying
x = 4

See similar equations:

| 242.36=29.3(5p-5) | | 9a+3b-4a+2b= | | 26=.5(4)(b+5) | | 163-7x=38x+23 | | 21g-7= | | 2(x+2)+4x=16 | | 8n-14=42 | | -5n=35 | | 18=12x-2x^2 | | 14-9x=184-44x | | n*3=n+6 | | 4x+24=-24 | | a=.5(6)(8+4) | | 3x+15=-95-7x | | 3(2t+8)=4(2+t) | | 3x-12-29=29-4x+7 | | -2(x+4)=-2x+9 | | 2x+3x-7=23 | | -10u+6=-8u-2 | | In(7x+8)=In(2x-22) | | 5(2r+23)-2=3 | | 3r+r=8 | | 9b+44=76 | | 36.7-42.42=42.42-x | | -36-2x=12-10x | | solveIn(7x+8)=In(2x-22) | | 4p^2q^2+20pq-24= | | 3(4x-2)+6= | | t=730+.15(16767-7300) | | 11x+6=6x-41 | | 7p+9q=48 | | 8y-7y+13=-31 |

Equations solver categories